Effects of Feed Moisture Content, Soybean Ratio and Barrel Temperature on Physical and Functional Properties of Extruded Maize-Soybean Flour Blends - Mugabi, Robert; Byakika, Stellah; Muzira Mukisa, Ivan (Tanzania Journal of Science, 2022)
The effects moisture content, temperature and soybean ratio on expanded product characteristics of extruded maize-soybean blends were studied. Response surface methodology was used to study the effects of extrusion conditions on extrudate properties taking barrel temperature (BT), feed moisture content (FM) and soybean flour ratio (SR) as factors. Expansion ratio (ER), water absorption index (WAI), water solubility index (WSI), hardness and colour (b* - (+) yellowness) of the extrudates were determined. BT and FM had significant effects on ER (p < 0.05). At low FM levels, ER increased with BT. It was observed that both FM and BT significantly affected WAI and WSI. WAI increased as FM increased. Increasing FM to 20% resulted in a decrease in WSI, beyond which an increase was observed. Hardness increased significantly as feed moisture content increased. High SR content significantly increased the extrudate hardness. FM had no significant effect on colour. Colour increased as the SR and BT increased. Significant regression models explained the effects of SR, FM, and BT on all response variables. All of the response variables' R2, were higher than 0.89.
Keywords: Maize; Soybean; Moisture content; Extrusion